Communication Assisted Protection Scheme Based on Artificial Neural Networks for Multi-Microgrid - Ali F. Qusayer; S. M. Suhail Hussain (IEEE Access, 2024)
Designing a properly coordinated protection scheme for a multi-microgrid is very challenging because of their distinct characteristics. A microgrid can be operated in a grid-connected mode through direct connection to utility or through another grid-connected microgrid. It can also operate in an islanded mode or get connected with another independent microgrid. The various operation modes and topologies under which the system may operate bring major challenges such as the bi-directional flow of power and substantial variation in fault current. Such characteristics make protection schemes of conventional radial distribution systems unreliable options. In this paper, a centralized communication-assisted protection scheme based on artificial neural networks is proposed. The scheme operates in a cascaded process. In the first stage, a central protection controller is responsible of identifying and isolating the microgrid or tie line which has the fault. In the second stage, the local protection controller will be activated due to detection of islanding condition. It will then identify and isolate the faulty line accordingly. Identification of fault location is accomplished through neural networks trained with massive amount of three phase voltage and current measurements of all buses and lines during different fault scenarios using MATLAB/Simulink environment. The proposed scheme utilizes IEC 61850 based standardized communication to monitor the multi-microgrid and send the trip commands. Finally, the performance evaluation of the proposed scheme in terms of end-to-end delays including neural networks computational delay and communication network delay through extensive simulations is also presented which proves the effectiveness of the proposed protection scheme.